Microstructure properties of particles reinforced polytetrafluoroethylene composite bearings after wear - Ünlü, B.S.; Uzkut, M.; Pi̇nar, A.M.; Özdi̇n, K. (Фізико-хімічна механіка матеріалів, 2015)
High-performance engineering polymers that ensure the desired properties for journal bearings and give good wear results are investigated. In this study, microstructure properties of polymer-based particle reinforced PTFE composite bearings have been determined by optical and SEM wear surface images.